1999
DOI: 10.1016/s0022-5223(99)70057-7
|View full text |Cite
|
Sign up to set email alerts
|

Forty-one years of surgical experience with congenital supravalvular aortic stenosis

Abstract: Results of operations for supravalvular aortic stenosis improved greatly after the introduction of more symmetric reconstructions of the aortic root. Multiple-sinus reconstructions (inverted bifurcated patch plasty and 3-sinus reconstruction) resulted in superior hemodynamics and were associated with reductions in both mortality rate and need for reoperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 27 publications
(28 reference statements)
1
87
1
Order By: Relevance
“…[52][53][54] Numerous investigators have reported that dilation of the coronary arteries is seen more frequently than stenosis. 41,[55][56][57] van Son and colleagues 50 reported that coronary ostial stenosis was more common than dilation in the left coronary artery, whereas dilation was more common than stenosis in the right coronary artery. Furthermore, Kim et al 41 reported that in those patients with the hourglass type of SVAS, 80% had coronary arterial dilation, whereas those with long-segment stenosis demonstrated coronary ostial stenosis.…”
Section: Coronary Artery Abnormalities In Svasmentioning
confidence: 99%
“…[52][53][54] Numerous investigators have reported that dilation of the coronary arteries is seen more frequently than stenosis. 41,[55][56][57] van Son and colleagues 50 reported that coronary ostial stenosis was more common than dilation in the left coronary artery, whereas dilation was more common than stenosis in the right coronary artery. Furthermore, Kim et al 41 reported that in those patients with the hourglass type of SVAS, 80% had coronary arterial dilation, whereas those with long-segment stenosis demonstrated coronary ostial stenosis.…”
Section: Coronary Artery Abnormalities In Svasmentioning
confidence: 99%
“…In a catheterization study of 26 patients with WBS, coronary artery dilation or stenosis was found in 27% (39). In mixed cohorts of individuals who had either WBS or mutations in the ELN gene in conjunction with severe SVAS requiring surgery, coronary disease was found in 28%-45% (49,50). Although coronary disease appears to be related to the severity of supravalvular aortic narrowing (39), case reports indicate that severe coronary artery disease leading to death may be the sole vascular feature in some patients with WBS (51,52).…”
Section: Clinical Features Of Wbsmentioning
confidence: 99%
“…The symmetric inverted 3-sinus patch plasty has resulted in improved outcome in one large series (49). Early mortality for repair of SVAS is 1%-9% (range of median or mean age at operation, 6-16 years), with 20-year survival of 77%-97% and longterm reduction in peak catheterization gradients in the majority of patients (36,49,95,97). Although gradients maybe relieved, hypoplasia may persist in the remainder of the aortic arch (98).…”
Section: Current Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, reconstruction of the aortic root with autologous pericardial patches in each sinus after transection of the aorta has the advantage of symmetry while restoring the normal aortic root anatomy (8,14,18) . This article encouraged our cardiac team to choose three-patch technique, while our decision making of surgical strategy.…”
Section: Discussionmentioning
confidence: 99%